2018
DOI: 10.3389/fmats.2018.00075
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic-Enhanced Organic Light-Emitting Diodes Based on a Graphene Oxide/Au Nanoparticles Composite Hole Injection Layer

Abstract: Organic light-emitting diodes (OLEDs) have drawn a great deal of attention due to their broad applications in lighting and displaying. With the development of nanotechnology, surface plasmas have been widely used in photonics, microscopes, solar cells and biosensors. In this paper, by inserting graphene oxide (GO), Au nanoparticles (Au NPs) and GO/Au NP composite structures between the hole transport layer (NPB) and indium tin oxide (ITO) anode, respectively, the electroluminescent performance of Alq 3-based O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The improvement of devices' performance can be attributed to the smooth ITO surface after the introduction of GO HIL and the reduced hole-injection barrier due to the high work function of GO. We also found the similar result in green OLED devices with the structure of ITO/GO/NPB/Alq 3 /LiF/Al [37].…”
Section: D Materials As Hole Injection Layer (Hil)supporting
confidence: 80%
“…The improvement of devices' performance can be attributed to the smooth ITO surface after the introduction of GO HIL and the reduced hole-injection barrier due to the high work function of GO. We also found the similar result in green OLED devices with the structure of ITO/GO/NPB/Alq 3 /LiF/Al [37].…”
Section: D Materials As Hole Injection Layer (Hil)supporting
confidence: 80%
“…Plasmonic NPs are widely studied for their strong scattering, absorption of light and fluorescence emission, enabling their application in several fields such as labeling, imaging, and electronics. In particular, the efficiency enhancement of optoelectronic devices, such as organic light emitting diodes (OLEDs) (Munkhbat et al, 2016;Feng et al, 2018), organic solar cells (Li et al, 2012;Vangelidis et al, 2018), and light-detectors (Xie et al, 2017), have been largely demonstrated and ascribed to the effect of their peculiar optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of Au and Ag reduces the work function of ITO due to the formation of dipoles at the interface and, therefore, reduces the hole injection barrier, which in turn creates a more efficient transfer to the HTL. In the device configuration of Figure 6a , a graphene oxide–Au nanocomposite HIL inserted between ITO and NPB was used to enhance the EL of Alq 3 -based OLED [ 51 ]. The correlation between the wavelength absorbed (≈540 nm) by AuNP and the PL emission of the Alq 3 thin film (≈530 nm) implies a suitable plasmonic coupling with the NPB HTL ( Figure 6b ).…”
Section: Reviewmentioning
confidence: 99%
“…(c) The electromagnetic field distribution around AuNP with 20 nm diameter simulated by finite-difference time-domain modelling. Figure 6a –c was adapted from [ 51 ] (© 2018 J. Feng et al, distributed under the terms of the Creative Commons Attribution 4.0 International License, https://creativecommons.org/licenses/by/4.0/).…”
Section: Reviewmentioning
confidence: 99%